A King Travels : Festive Traditions in Late Medieval and Early Modern Spain - Ruiz, Teofilo F., 1943- (Book collections on Project MUSE., 2012)
A King Travels examines the scripting and performance of festivals in Spain between 1327 and 1620, offering an unprecedented look at the different types of festivals that were held in Iberia during this crucial period of European history. Bridging the gap between the medieval and early modern eras, Teofilo Ruiz focuses on the travels and festivities of Philip II, exploring the complex relationship between power and ceremony, and offering a vibrant portrait of Spain's cultural and political life. Ruiz covers a range of festival categories: carnival, royal entries, tournaments, calendrical and n.